Differential Apoptotic and Mitogenic Effects of Lectins in Zebrafish - Wang, Kaidi; Liu, Chengdong; Hou, Yiying; Zhou, Huihui; Wang, Xuan; Mai, Kangsen; He, Gen (Frontiers in Endocrinology, 2019)
Plant lectins represent a major group of anti-nutritional factors that can be toxic to human and animals. However, the mechanisms by which lectins regulate cell fates are not well-understood. In the present study, the cellular and molecular impacts of three common lectins, agglutinins from wheat germ [wheat germ agglutinin (WGA)], soybean [soybean agglutinin (SBA)], and peanut [peanut agglutinin (PNA)] were examined in zebrafish embryo and liver cells. WGA and SBA were found to induce cell apoptosis both in vitro and in vivo, while PNA stimulated cell proliferation. WGA and SBA reduced levels of B cell lymphoma-2 (Bcl-2), phosphorylation of Bcl-2-associated death promoter (Bad), cyclin-dependent kinase 4 (Cdk4), and phosphorylation of the retinoblastoma (Rb). WGA and SBA also inhibited the activities of cell survival pathways including protein kinase B (Akt), extracellular signal-regulated protein kinases 1 and 2 (Erk1/2), and target of rapamycin (Tor). Furthermore, WGA and SBA shifted the cellular metabolism characterized by reduced expression of glucose-6-phosphate dehydrogenase (g6pd) and increased expression of glutamine synthetase (glul) and glutamate dehydrogenase (glud). However, PNA showed the opposite effects toward these molecular markers compared to those of WGA and SBA. Therefore, our results revealed some plant lectins (WGA and SBA) were toxic while the other (PNA) was mitogenic. Further characterization of the distinct functions of individual lectins should be valuable for both nutrition and other potential applications.